Nazi Exhibition Design and Modernism - Tymkiw, Michael, 1972- (Book collections on Project MUSE., 2018)
"While National Socialist exhibitions are seen as platforms for attacking modern art, they also served as sites of surprising formal experimentation among artists, architects, and others, who often drew upon the practices and principles of modernism when designing exhibition spaces. Michael Tymkiw reveals that a central motivation behind such experimentation was the interest in provoking what he calls "engaged spectatorship.""--